2021
DOI: 10.1002/jpen.2248
|View full text |Cite
|
Sign up to set email alerts
|

Impact on caregivers of adult patients receiving parenteral support for short‐bowel syndrome with intestinal failure: A multinational, cross‐sectional survey

Abstract: Background: Patients with short-bowel syndrome and intestinal failure (SBS-IF) require parenteral support (PS) and may need long-term home-care support. This survey assessed the impact of care provision on adult caregivers of adult patients receiving PS for SBS-IF.Methods: An online, cross-sectional survey of caregivers of adults with a self-reported physician diagnosis of SBS-IF was conducted in France, Germany, Italy, the UK, and USA. Impact on caregivers was evaluated using the 18-item Caregiver Strain Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…A trend of a higher caregiver burden in functionally limited patients was observed 15 . More recently, Jeppesen et al demonstrated that informal caregivers experienced emotional and professional impairments linked to their caregiver role and fears about the patient's health 10 . Based on these findings and available data, a close management after hospital discharge with trained rehabilitation services and referral centers with expert HPN teams (including pivotal nurses, dietitians specialized in IF, and physicians) should be a part of management of patients with CIF, especially for isolated patients 16 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A trend of a higher caregiver burden in functionally limited patients was observed 15 . More recently, Jeppesen et al demonstrated that informal caregivers experienced emotional and professional impairments linked to their caregiver role and fears about the patient's health 10 . Based on these findings and available data, a close management after hospital discharge with trained rehabilitation services and referral centers with expert HPN teams (including pivotal nurses, dietitians specialized in IF, and physicians) should be a part of management of patients with CIF, especially for isolated patients 16 .…”
Section: Discussionmentioning
confidence: 98%
“…15 More recently, Jeppesen et al demonstrated that informal caregivers experienced emotional and professional impairments linked to their caregiver role and fears about the patient's health. 10 Based on these findings and available data, a close management after hospital discharge with trained rehabilitation services and referral centers with expert HPN teams (including pivotal nurses, dietitians specialized in IF, and physicians) should be a part of management of patients with CIF, especially for isolated patients. 16 It seems important to give priority to the development of these structures and to facilitate patients' and caregivers' access to the various resources available (such as patient organizations or therapeutic education workshop) to decrease strains and to raise awareness of caregiver burden among patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…32 The impact on caregivers supporting patients with SBS-IF was recently reported. 19 Much like the patients in this study, caregivers reported difficulty with working full-time and spending time with family and friends.…”
Section: Discussionmentioning
confidence: 67%
“…The instrument generates four scores that relate to absenteeism, presenteeism, work productivity, and activity impairment. The scores are given as percentages, with higher values indicating greater impairment and reduced work productivity 19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation